Representações sociais de professoras sobre as relações étnico-raciais na educação infantil em Bragança-PA - REIS, Maiara da Silva (2022)
This study analyzes the Social Representations of teachers on Ethnic-Racial Relations in Early Childhood Education in Bragança-PA. This research was based on the theoreticalmethodological framework based on the Theory of Social Representations of Moscovici (1978) and on the discursive dialogism of BAKHTIN (2011). For a discussion about Ethnic-Racial Relations and Early Childhood Education we spoke with Silva (2007), Gomes (2005), Santos (2009), Cavalleiro (2006), Corrêa (2019), Munanga (2001), for the discussion of race relations and Piaget (1994), Ariés (1981), Kramer 1999), Oliveira (1993) for the foray on Early Childhood Education. The study is a research with a qualitative approach in which we used questionnaire and observation data collection instrument, in which four teachers participated, who teach in Early Childhood Education in a public school in the city of Bragança / PA. According to the Moscovi Tridimensionality (1978) in the “Image” dimension, the teachers' objectifications reveal a stereotyped image of the black child, linked to a disadvantaged social class that they inferiorize and place them in an irrelevant position in relation to the white child. In the “Information” dimension, the teachers' representational field reveals little knowledge for dealing with Ethnic-Racial Relations in Early Childhood Education, which culminates in the trivialization of racism at school, making it difficult to build the identity of black students. The “Attitude” dimension reveals that teachers and the school itself do not offer students a diversified education based on ethnic-racial relations, teachers have difficulty and lack of information to reverse situations of racism among students, which reveals the importance the insertion of studies for Ethnic-Racial Relations promoting a diversified and multicultural education. It is concluded that teachers do not recognize that children at this level of education perceive the differences in their racial belonging, hiding a reality that is exposed in their own behaviors, attitudes and words. This shows that teachers still do not have the necessary knowledge to deal with Ethnic-Racial Relations, to contribute to the subversion of discriminatory practices in early childhood education. For this, it is necessary in addition to regular training in the pedagogical area, the continuation of specific in-depth studies on ethnicracial relations, so that Basic Education teachers are better informed about the laws and public policies that imply in the exercise of their work. In this way, the teacher will have a better direction for his practices in the classroom, with his pedagogical material more developed, thus being able to direct his students to a culturally and truly diversified education.